1988
DOI: 10.1099/00221287-134-9-2543
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviour and Mating System of Botryotinia fuckeliana, Teleomorph of Botrytis cinerea

Abstract: Analysis of 213 field isolates of Botrytis cinerea and 240 ascospore isolates of its sexual form Botryotinia fuckeliana indicated that sexual compatibility of this fungus is controlled by a single mating type gene with two alleles. Most isolates were heterothallic, that is, they were self-sterile and able to produce ascospore progeny when crossed with reference strains carrying the mating type gene MATI-1 or MATI-2. About 16% of the field isolates and 6% of the ascospore progeny were homothallic, that is, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
0
14

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 30 publications
2
96
0
14
Order By: Relevance
“…This study revealed a genetic diversity of up to 99% for the B. elliptica field population, in agreement with a previous study of B. elliptica isolates collected from several regions in the USA and Taiwan, using RAPD markers (Huang et al, 2001). Interestingly, levels of genotypic diversity of B. elliptica in our study are as high as reported for B. cinerea, a species that infects multiple host plants and reproduces sexually in the field (Faretra, Antonacci, & Pollastro, 1988;Giraud et al, 1997). It should be noted that it is difficult to compare levels of genetic diversity obtained with different markers and different sample sizes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study revealed a genetic diversity of up to 99% for the B. elliptica field population, in agreement with a previous study of B. elliptica isolates collected from several regions in the USA and Taiwan, using RAPD markers (Huang et al, 2001). Interestingly, levels of genotypic diversity of B. elliptica in our study are as high as reported for B. cinerea, a species that infects multiple host plants and reproduces sexually in the field (Faretra, Antonacci, & Pollastro, 1988;Giraud et al, 1997). It should be noted that it is difficult to compare levels of genetic diversity obtained with different markers and different sample sizes.…”
Section: Discussionsupporting
confidence: 79%
“…In a natural population of Cryphonectria parasitica, parasexual recombination has been reported to occur even between vegetatively incompatible individuals (McGuire et al, 2005). The presence of heterokaryons in natural populations of B. cinerea (Faretra et al, 1988;Pollastro, Faretra, Canio, & De Guido, 1996) provides a possibility for mitotic recombination. Unfortunately, knowledge about heterokaryosis or mycelial (in)compatibility in B. tulipae is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Microconidia are uninucleate and function primarily as spermatia (12,58) and are not able to germinate and grow on agar media (14,19). In studies of aerobiology, fungi are traditionally quantified as culturable units on agar media and hence microconidia are not quantified.…”
Section: Discussionmentioning
confidence: 99%
“…However, homothallic (self-fertile) strains and heterokariotic strains with MAT1-1 and MAT1-2 nuclei have been reported (Faretra et al, 1988;van Kan et al, 2010). The presence of sexually compatible strains has been demonstrated in B. cinerea in Chile (Faretra and Latorre, 2007).…”
Section: The Pathogenmentioning
confidence: 99%
“…B. cinerea produces macroscopic, stipitate apothecia that originate from sclerotia (Faretra and Antonacci, 1987) (Figure 2D). Nevertheless, the sexual stage rarely occurs in nature, but apothecia and ascospores can be obtained under controlled laboratory conditions (Faretra and Antonacci, 1987;Faretra et al, 1988).…”
Section: The Pathogenmentioning
confidence: 99%